Estudo da fotooxidação de nanocomposito PP/bentonita - Bar, Marcia (2008)
The cation exchange of the bentonite and its processing are important factors to the polimeric nanocomposite formulation. The objective of this work was to produce nanocomposites of polypropylene / sodium bentonite and polypropylene / organophilic bentonite through melt intercalation and analyze the degradation produced by ultraviolet irradiation. Cetyl trimethyl ammonium bromide (C17H38BrN), Cetremide®, was used to organophilize the bentonite clay. Corotating twin screw extruder was used to process the nanocomposite; injection molded specimens were used for the flexural test and optical micrographs; hot pressed samples were used for DSC, XRD and FTIR. The XRD results showed that the samples of nature bentonite obtained better interaction with de polymer rather than treated clay, and produced intercalated nanocomposite. The degradation by ultraviolet irradiation was observed after 24 hours of exposition. All the samples showed the same photoproducts and at the same proportion until 240 hours of UV exposition; at higher times, 480 hours of UV exposition, the organophilize bentonite composite showed higher degradation than other ones. The flexural modulus decreased with degradation time. The degradation occurs due chromophores impurities presented in the samples, thus samples with clay show higher degradation, and organophilic clay contains ammonium salt that contribute to increase the degradation.